High-Vacuum Drainage System in Percutaneous Image-Guided Thoracocentesis for Complex Pleural Effusions - Jiawei Alexander Yap; Krishna Mohan Gummalla; Martin Weng Chin H'ng (Journal of Clinical Interventional Radiology ISVIR)
Purpose Our retrospective study is aimed to analyze the efficacy and outcomes between high-vacuum suction drain (HVSD) over passive drainage in the setting of percutaneous image-guided thoracocentesis, with a secondary aim to determine if preprocedural computed tomography (CT) can aid decision-making.